Upaya Peningkatan Stamina Melalui Therapi Akupressure Pada Pasangan Usia Subur (PUS) Di Desa Kungkai Baru Seluma - Rahmawat, Dyah Tepi i; Metasari, Des; Diniarti, Fiya; Sofais, Danur Azissah R.; Syafrie, Ice Rakizah; Cempaka, Febri Melati; Oktavia, Putri Anggun; Dilla, Milka Pinta; Anggelina, Novtiara (Jurnal Dehasen Mengabdi, 2023)
Acupressure is a type/method of health care that is carried out through pressure techniques on the body's surface on acupuncture points using fingers, or other body parts, or blunt-tipped devices for health purposes (Ministry of Health, 2021). The acupressure method prioritizes promotive and preventive. Acupressure is a form of traditional health service by stimulating certain points by pressing on the surface of the body using fingers or blunt objects for fitness purposes or to help overcome health problems. Couples of childbearing age are couples who are at a productive age. such as pregnancy, childbirth etc. Acupressure in fertile couples is very useful to increase stamina so that it can improve the health of the PUS, the increase in the health of the PUS will have an impact on the reproductive health of the PUS itself.